2018
DOI: 10.1111/myc.12737
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy and biopsy study of paracoccidioidomycosis and neuroparacoccidioidomycosis with and without HIV co‐infection

Abstract: Paracoccidioidomycosis (PCM) is a systemic mycosis prevalent among immunocompetent patients in Latin America. This study aimed to describe the frequency, demographics and clinical characteristics of central nervous system PCM (NPCM) and PCM in an endemic region, and the impact of human immunosuppression virus (HIV) co-infection. This was a retrospective study of autopsy and biopsy reports from the Medical Pathology Section of the Hospital de Clinicas, UFPR, Curitiba, Southern Brazil, between 1951 and 2014. PCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…NPCM prevalence among PCM cases in the literature varies depending on the methodology used for investigation and the studied area. It ranges from 3.4% to 13.9% in some retrospective cohort studies [7,8], reaching 36.0% in necropsy evaluations [9,10]. Imaging studies using computerized tomography (CT) showed a prevalence of 12.5% for NPCM among PCM patients without neurologic symptoms [11].…”
Section: Discussionmentioning
confidence: 99%
“…NPCM prevalence among PCM cases in the literature varies depending on the methodology used for investigation and the studied area. It ranges from 3.4% to 13.9% in some retrospective cohort studies [7,8], reaching 36.0% in necropsy evaluations [9,10]. Imaging studies using computerized tomography (CT) showed a prevalence of 12.5% for NPCM among PCM patients without neurologic symptoms [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary findings may be localized or may be part of a more disseminated disease. [7][8][9][10][11] A small number of patients remain subclinical. Acute lung infection rapidly spreads to the lymph nodes, liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological findings are unspecific, and include micronodular infiltrates, foci of consolidation, cavities, fibrosis or, infrequently, calcified nodules. [7][8][9][10][11] The histopathological findings range from neutrophilic microabscesses, scattered interstitial necrotizing granulomas, and consolidative granulomatous pneumonia. Progressive pulmonary disease is more common than acute/subacute lung involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included autopsy reports between 1951 and 2014 and biopsy reports from 1954 to 2014. PCM and NPCM diagnosis criteria were described previously . PCM (systemic PCM and NPCM) was diagnosed in 381 cases, in this period; 199 cases were excluded (135 cases because CNS autopsy was not performed, in 39 the medical charts could not be located or there was no information about the city of origin, and 25 cases were from other states).…”
Section: Methodsmentioning
confidence: 99%